2021
DOI: 10.3390/ijerph18094411
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Kinesiology Taping Stretch Tensions on Soleus and Gastrocnemius H-Reflex Modulations

Abstract: This study examined the acute effects of stretch tensions of kinesiology taping (KT) on the soleus (SOL), medial (MG), and lateral (LG) gastrocnemius Hoffmann-reflex (H-reflex) modulation in physically active healthy adults. A cross-over within-subject design was used in this study. Twelve physically active collegiate students voluntarily participated in the study (age = 21.3 ± 1.2 years; height = 175.6 ± 7.1 cm; body weight = 69.9 ± 7.1 kg). A standard Y-shape of KT technique was applied to the calf muscles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Finally, this study did not explore the physiological mechanisms underlying the observed increase in DFA. Previous studies have examined factors such as changes in skin blood flow 22 ) and the excitability of motor neurons 23 ) in relation to elastic tape application; however, these factors were not investigated in this study. In addition, the impact of physiological phenomena represented by the alpha-gamma linkage and the axon reflex on the intraweight muscle should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study did not explore the physiological mechanisms underlying the observed increase in DFA. Previous studies have examined factors such as changes in skin blood flow 22 ) and the excitability of motor neurons 23 ) in relation to elastic tape application; however, these factors were not investigated in this study. In addition, the impact of physiological phenomena represented by the alpha-gamma linkage and the axon reflex on the intraweight muscle should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent work conducted by Chen et. al on the triceps surae muscle during both lying and standing postures indicates that the change in intensity of tension of the KT does not have much effect on the spinal motor neuron excitability; therefore, in terms of modifying sensory-motor activity, the tension applied during a KT application should not be an issue [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%